2006
DOI: 10.1002/elsc.200520133
|View full text |Cite
|
Sign up to set email alerts
|

Decolorizing Reactive Textile Dyes with White‐Rot Fungi by Temporary Immersion Cultivation

Abstract: The decontamination of effluents from textile industries is problematic due to the fact that textile dyes are resistant to degradation in the environment. Enzymes from white rot fungi, especially laccase, are able to degrade various complex aromatic structures, and are therefore able to decolorize textile dyes. The white‐rot fungi Trametes versicolor and Phanerochaete chrysosporium were immobilized, separately, on both pine wood chips and palm oil fiber, and cultivated in the temporary immersion RITA® (Récipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Immobilised fungal phytase production on 6 th day employing adsorption and entrapment technique however, it was subjected to microbial decomposition easily and not durable for a long term production. Permanent loss of enzymes from fungal extracellular matrix due to degradation and loss of supporting material concerned with waste water treatment has been reported by Bohmer et al [41]. Results from the present study indicated that Poly Urethane Foam was a better immobilisation matrix for proliferation of fungus.…”
Section: Phytase Production By Immobilised Fungus Employing Adsorptionsupporting
confidence: 70%
“…Immobilised fungal phytase production on 6 th day employing adsorption and entrapment technique however, it was subjected to microbial decomposition easily and not durable for a long term production. Permanent loss of enzymes from fungal extracellular matrix due to degradation and loss of supporting material concerned with waste water treatment has been reported by Bohmer et al [41]. Results from the present study indicated that Poly Urethane Foam was a better immobilisation matrix for proliferation of fungus.…”
Section: Phytase Production By Immobilised Fungus Employing Adsorptionsupporting
confidence: 70%
“…The strain was found to be utilizing pineapple leaves, an inexpensive, unused agro-residue, as substrate for laccase production. The initial laccase activity expressed by Marasmiellus palmivorus LA1 was as good as or even higher than that of the initial activities of some of the other reported fungi [ 35 38 ]. The present study applies taguchi method for the optimization of extracellular laccase enzyme production in SSF from the fungi Marasmiellus palmivorus LA1.…”
Section: Introductionmentioning
confidence: 83%
“…In bioprocessing of chitinases, interesting results were obtained in our research on the cultivation of P. alliaceus H5 in temporary immersion systems (results to be published). Few publications are available on the cultivation of fungi and enzyme production in such systems .…”
Section: Future Prospectsmentioning
confidence: 99%